Strategi Pengelolaan Sampah di TPA Lubuk Terentang: Tinjauan Analisis SWOT - Muliyadi Muliyadi; Fuad Muchlis; Hutwan Syarifuddin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
People create waste as a by product of their actions, which results in an overall increase in the amount of waste produced. Because of this, it is essential to carry out waste management in an effective and efficient way. This study aims to investigate the waste management strategy used by the Environmental Service at the Lubuk Terentang Landfill located in the Lubuk Terentang Village in the Betara District of the Tanjung Jabung Barat Regency. This study employs descriptive research methods and uses a qualitative data collection approach. Informants for this study include members of the Waste and Hazardous Waste Management Section, the Regent and Deputy Regent, Bapedda, and inhabitants of the surrounding area who volunteered to participate in the study. The gathering of data and information involved interviews and documentation of various kinds. The SWOT analysis methodology is a data analysis technique that considers all internal and external features, including strengths, weaknesses, opportunities, and threats. This position reveals that both opportunities and weaknesses have negative and positive values, indicating that the landfill in its management faces enormous opportunities. Still, on the other hand, the landfill faces several obstacles or internal weaknesses. The results of the SWOT analysis place the Lubuk Terentang Landfill in the third quadrant (negative, positive). From this strategy, two alternative approaches can be obtained: first, the procurement and repair of facilities, and second, increasing the ability to finance operational investment and waste maintenance. The focus of the waste management strategy in the landfill is to minimize the landfill's internal problems so that it can seize great opportunities, often referred to as a turnaround strategy.